P‐101: In‐situ Fabrication Strategy of Perovskite Quantum Dots for Novel Display Technology. Issue 1 (25th September 2020) - Bai, Zelong; Li, Jing; Zhang, Tao; Li, Fei; Liu, Ruikuo; Qiu, Shize; Zhang, Rongjian; Zhong, Haizheng
Abstract : In‐situ fabrication strategy of perovskite quantum dots is a state‐of‐art manufacturing technique for highly efficient color convertor film/layer. By using this technique, we can economically achieve high‐efficient and ultra‐thin quantum dots color convertor layer simply through roll‐to‐roll coating process or ink‐jet printing process. Here, we will thoroughly introduce the benefits of in‐situ fabrication strategy and several featured products designed with this concept.